Linguistic Manipulation and Logical Fallacies: How Frank Underwood Constructs Verbal Traps to Influence Audience Perception in House of Cards - Ewald J. Marković (Journal of Linguistics and Communication Studies, 2025)
Frank Underwood, the central figure in House of Cards, exemplifies the strategic use of linguistic manipulation to consolidate power, disarm adversaries, and influence public perception. This paper examines how Underwood constructs verbal traps using logical fallacies such as ad hominem attacks, false dilemmas, appeals to emotion, post hoc reasoning, and straw man arguments. By analyzing the frequency and contextual deployment of these fallacies in his monologues and dialogues, this study highlights how Underwood tailors his rhetorical approach depending on whether he is persuading the audience or coercing opponents. His monologues serve as narrative control mechanisms, using emotional appeals and causal distortions to justify his actions, while his dialogues function as battlefields of manipulation, where he employs character attacks, forced choices, and misrepresentations to dominate his rivals. Through a quantitative analysis of his speech patterns, this paper reveals the systematic nature of Underwood’s linguistic deception and its broader implications for political rhetoric. The study concludes by drawing parallels between Underwood’s strategies and real-world political discourse, emphasizing the dangers of uncritical acceptance of rhetorical persuasion in governance and media.